Peran Kepercayaan Kesehatan dan Literasi Kesehatan Terhadap Kepatuhan Pengobatan Antibiotik Pasien Pengguna Konsultasi Kesehatan Daring - Farah Fauziyah; Diana Setiyawati (INSAN Jurnal Psikologi dan Kesehatan Mental, 2025)
Adherence is a critical component in the success of treatment and the prevention of antibiotic resistance. Patient adherence to antibiotic treatment obtained from online consultation services is influenced by health beliefs and health literacy.  This study hypothesized that health beliefs and health literacy would predict antibiotic treatment adherence among users of online health consultation services. A quantitative survey approach was conducted with 210 participants who had used online health consultation, received at least one antibiotic medication, and were aged 18 years or older. Data were analyzed using multiple linear regression. The findings indicated that health beliefs significantly predicted antibiotic adherence among online health consultation users, whereas health literacy did not have a significant effect. Further exploration revealed a moderating role of educational attainment in the relationship between health literacy and adherence. These results highlight the important of patient-related internal factors in influencing antibiotic adherence among users of online health services.